Potential and Ecotourism Development in The Wee Boro Lake, Tebara Village, West Sumba District: Potensi dan Pengembangan Ekowisata di Kawasan Danau Wee Boro, Desa Tebara, Kabupaten Sumba Barat - Yus Sudarsono Muslim; Gatot Yulianto (Department of Aquatic Resources Management, Faculty of Fisheries and Marine Science, IPB University, 2025)
Wee Boro Lake is located in Tebara Village, West Sumba Regency. Wee Boro Lake was widely promoted as a tourist attraction on May 31 2023 and was attended by the regent of West Sumba, all village heads in West Sumba Regency, as well as other important stakeholders. Wee Boro Lake is located at the coordinates (°39'54